2011
DOI: 10.4103/0973-6247.83235
|View full text |Cite
|
Sign up to set email alerts
|

Attitude to blood donation in Saudi Arabia

Abstract: Background and Objectives:The blood donor system in the Kingdom of Saudi Arabia depends on a combination of voluntary and involuntary donors. The aim of this study is to explore the attitudes, beliefs and motivations of Saudis toward blood donation.Materials and Methods:The study was conducted at the Donor Centers at King Khalid University Hospital (KKUH) Blood Bank and King Saud University Students Health Center, Riyadh. A self-administered questionnaire was distributed to donors (n = 517) and nondonors (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 28 publications
6
61
2
Order By: Relevance
“…Education remained a significant predictor of knowledge level after adjusting for all possible confounders. The overall attitude of the studied subjects was neutral, with only 31.6% reporting a positive attitude to donation, a figure that reflects generally, an unfavorable attitude to donation, compared to 99% in a previous study by Abdel Gader et al21 This unfavorable attitude to donation in the present study may reflect the possible negative impact of an incident of HIV transmission to a young Saudi girl following blood transfusion24 on public perception to donation. Males had a better attitude than females, which is the opposite of what had been found in a similar study 13.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Education remained a significant predictor of knowledge level after adjusting for all possible confounders. The overall attitude of the studied subjects was neutral, with only 31.6% reporting a positive attitude to donation, a figure that reflects generally, an unfavorable attitude to donation, compared to 99% in a previous study by Abdel Gader et al21 This unfavorable attitude to donation in the present study may reflect the possible negative impact of an incident of HIV transmission to a young Saudi girl following blood transfusion24 on public perception to donation. Males had a better attitude than females, which is the opposite of what had been found in a similar study 13.…”
Section: Discussioncontrasting
confidence: 76%
“…This may explain why transmission of infection was not stated as a reason for not donating in the current study. Fear has been considered as the most commonly reported negative attitude on blood donation 2,13,14,18,21. In the current study, fear of the sight of blood was the reason for not donating in 6% and 11% of males and females, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…Our results are similar to several other studies. 1 , 6 , 9 A study in a poor locality in India observed the most common reason of not donating blood was the thinking that blood donation has harmful effects (50%) and many people said that they don’t have any reason to donate blood (25%). 18 There is utmost need to approach those people who have never been approached and they intend to donate blood.…”
Section: Discussionmentioning
confidence: 99%
“…The state-of-the art hospitals are providing free and highly specialized services, like open heart surgery, transplant surgeries, cancer treatment, and also providing blood to patients of bleeding disorders, and other hematological disorders. 1 All these services require ample and continuous blood supply from donors. Another imperative factor in KSA is road traffic accidents which needs lot of blood on emergency basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation